Does students' empowerment influence their commitment?. (1st January 2012) - Shafaei, Azadeh; Nejati, Mehran
Students' commitment plays a very important role in their academic achievement. This paper seeks to investigate how various aspects of students' empowerment influence their commitment, by investigating a sample 59 undergraduate students. Results of the study revealed that out of the four categories of empowerment, only self-determination significantly enhanced students' commitment. Hence, it was argued that to enhance students' commitment, which can consequently result in their improved sense of belongingness, schools need to enhance their students' perceived sense of having selection in initiating and regulating actions within the school setting. Findings of this study provide invaluable insights for educational administrators and school deans to enhance students' empowerment, which might be through engaging them in school affairs and involving them in some of activities and decisions of the school.